Health Promotion Actions and School Violence—A Cluster Analysis from Finnish Comprehensive Schools - Ellonen Noora; Pasanen Miko; Wiss Kirsi; Mielityinen Laura; Lähteenmäki Elina; Joronen Katja (International Journal of Environmental Research and Public Health, 2022)
(1) Schools have a significant role in violence prevention activities. This study aimed to first identify profiles of Finnish comprehensive schools based on school violence. The second aim was to examine the associations between profiles concerning health promotion actions, reactive or punitive actions, and school characteristics. (2) The study used the large-scale, nationally representative Benchmarking System of Health Promotion Capacity-Building (BSHPCB) data (n = 2057 schools) completed by the school’s principal together with a student welfare team. The data was analyzed by cluster analysis and Chi-squared and Kruskal–Wallis tests. For post hoc testing, Fisher’s exact test with odds ratios and Mann–Whitney U-test were used. (3) The cluster analysis yielded five profiles of school violence: “No violence”, “Adolescent violence” (violence both among pupils and from pupils towards staff, but not inappropriate behavior from school staff towards pupils), “Not known” (principals either did not respond to these questions or they did not know whether there had been any school violence incidents), “Peer violence” (school violence occurred among pupils but not from pupils towards staff, nor inappropriate behavior from school staff towards pupils), and “All violence” (all types of school violence and inappropriate behavior from school staff towards pupils). These clusters differed according to type of school and municipality. Additionally, both management and monitoring as health promotion actions were related to higher incidence of school violence whereas other actions, such as commitment, resources, common practices, and participation were not related to school violence. (4) The findings of this study indicate that schools have different profiles in terms of school violence and providing evidence and guidance for school violence prevention work.